CLASSROOM ACTION RESEARCH: USING COOPERATIVE LEARNING (TEAM PAIR SOLO) TO IMPROVE NURSING STUDENTS’ SPEAKING SKILL - Wahyu Wibisono (Universitas Islam Lamongan, 2018)
Mastering many languages is a softskill that every nurse must acquire in order to make patients feel comfortable and decrease the anxiety.. English is one of many languages which is widely used in the world. So, it is important to a nurse to be able to communicate using English. This research was intended to apply cooperative learning TPS (Team Pair Solo) as the technique to enhance students’ English-speaking skill when they took the “communicating class” in the fifth semester in Stikes Patria Husada Blitar. This research was a Classroom Action Research. The subject was 10 students of the fifth semester. The researcher used several instruments; such as observation checklist, field notes, test, and questionnaire. The findings showed that TPS were effective in improving the speaking skill of the student in class. This could be seen by the increase of students’ mean scores in the test results 65.1 in preliminary study became 81.3 in the first cycle and this also meant that 100% students could pass the minimum passing grade of 78 which was setted by the researcher as the criteria of success of the research itself. The improvement could also be seen on the results of the field notes that showed positivity, raise of motivation, and good responses from the students. It showed that by using cooperative learning (Team Pair Solo), students’ motivation and self-esteem increased since the TPS could accommodate students to be well prepared before they speak by discussing in team, pair with other student, and finally they have great self-esteem to stand by their self infront of the class. Other researchers were expected to elaborate this cooperative learning with other technique so that there would be alot of technique could be used as reference in teaching English